INEQUALITY AND MINIMUM WAGE POLICY IN MEXICO: A COMMENT - Cabral, René (Investigación Económica, 2016)
While its structure is not that of a typical research paper, this work by Krozer, Moreno and Rubio (2015) makes a contribution to the recent debate about raising the minimum wage in Mexico. The paper provides a comprehensive account of the evolution of income distribution in Mexico as measured by the Gini index, poverty headcount, income per capita across deciles, top and bottom income shares, and, most importantly, the functional distribution of household income (labor, capital and transfer income components). In general, in this policy-oriented paper the authors argue in favor of a minimum wage raise and advocate in the conclusions for a minimum wage initiative approval in the near future...